Fangchinoline alleviates cognitive impairments through enhancing autophagy and mitigating oxidative stress in Alzheimer’s disease models - Yi, Lilin; Luo, Man; Wang, Maoju; Dong, Zhifang; Du, Yehong (Frontiers in Cell and Developmental Biology, 2023)
Introduction: Alzheimer’s disease (AD) is a debilitating, progressive, neurodegenerative disorder characterized by the deposition of amyloid-β (Aβ) peptides and subsequent oxidative stress, resulting in a cascade of cytotoxic effects. Fangchinoline (Fan), a bisbenzylisoquinoline alkaloid isolated from traditional Chinese herb Stephania tetrandra S. Moorec, has been reported to possess multiple potent biological activities, including anti-inflammatory and antioxidant properties. However, the potential neuroprotective efficacy of Fan against AD remains unknown. Methods: N2AAPP cells, the mouse neuroblastoma N2A cells stably transfected with human Swedish mutant APP695, were served as an in vitro AD model. A mouse model of AD was constructed by microinjection of Aβ1–42 peptides into lateral ventricle of WT mice. The neuroprotective effects of Fan on AD were investigated through a combination of Western blot analysis, immunoprecipitation and behavioral assessments. Results and discussion: It was found that Fan effectively attenuated the amyloidogenic processing of APP by augmenting autophagy and subsequently fostering lysosomal degradation of BACE1 in N2AAPP cells, as reflected by the decrease in P62 levels, concomitant with the increase in Beclin-1 and LC3-II levels. More importantly, Fan significantly ameliorated cognitive impairment in an Aβ1–42-induced mouse model of AD via the induction of autophagy and the inhibition of oxidative stress, as evidenced by an increase in antioxidants including glutathione reductase (GR), total antioxidant capacity (T-AOC), nuclear factor erythroid-2-related factor 2 (Nrf2), heme oxygenase-1 (HO-1), and superoxide dismutase-1 (SOD-1) and a decrease in pro-oxidants including hydrogen peroxide (H2O2) and inducible nitric oxide synthase (i-NOS), coupled with a reduction in apoptosis marker, cleaved caspase-3. Taken together, our study demonstrate that Fan ameliorates cognitive dysfunction through promoting autophagy and mitigating oxidative stress, making it a potential therapeutic agent for AD.